Dampak Bencana terhadap Ketahanan Pangan di Kabupaten Sukabumi - Sukmawani, Reny; Astutiningsih, Endang Tri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Food security must be realized down the household level wherever and under any conditions.  This study aims to determine the impact of landslides on food security in Sukabumi Regency.  The method used in this research is a survey method with the respondents in this study are households who are victims of land shifts in Nyalindung, Sukabumi Regency.  Data were analyzed using descriptive analysis.  The results showed that the landslide disaster has had an impact on decreasing household income and food security.  The food availability shows that staple food (rice) is always available, although most of them only have supplies for the next two days and still depend on products from outside their area.  From the aspect of affordability, it shows that it is not difficult for households to get rice, but it is difficult to find alternatives.  Households also find it difficult to get sources of protein other than salted fish and eggs, because they are rarely available and/or not always affordable to buy.  In terms of utilization, household food consumption patterns are less varied, especially for sources of carbohydrates and animal protein. So that, to be able to help improve the condition of food security, the use of yard land for farming (P2L) can be used as an alternative activity.